Analisis Kandungan Logam Berat Ikan Pelagis Kecil R. kanagurta, Decapterus sp dan S. crumenophthalmus Yang Tertangkap di Perairan Sekitar Bitung - Hetty M.P Ondang; Fidel J. Ticoalu; Rudi Saranga (Politeknik Kelautan dan Perikanan Bitung, 2020)
Technological developments have encouraged the growth of various industries, which on the onehand can increase economic growth, but on the other hand, it can also cause environmentaldamage as a result of negative impacts resulting from waste generated. The coastal and marinewaters of Bitung City are industrial dense areas which are spread from the northern to thesouthern region. Besides that there were activitied which adding to the increasingly denseactivities in the coastal waters of Bitung City like the ferry port, cargo and container ports, andpassenger port. The research aims to analyze the level of pollution of mercury heavy metals(Hg), lead (Pb), and cadmium (Cd) in several types of fish consumption from Bitung waters; toget the dominant type of heavy metal exposed to fish meat; and determine the level of heavymetal contamination in the waters around Bitung based on bio-indicators.The results ofresearch showed that all fish samples were contaminated by heavy metals and each location forsampling levels of metal contamination based on bio-indicators was different, where the watersof Kampung Pisang have a higher level of metal contamination.